Progetto Civitella d'Agliano 1991. - Carboni, Massimo; Karkow, Stefan; Rahmann, Fritz; Rauch, Iwona; Schröder, Johannes Lothar; Steiger, Silvia; Tsangaris, Manos; Van Soest, Trudy; Zickfeld, Carla; van der Heyden, J.C.J. (Civitella d'Agliano, 1991)
Domburg, Bart ; Gallio, Christoph ; Giagni, Riccardo ; van der Heyden, J.C.J. ; Mark, Helmut ; Rahmann, Fritz ; Streuli, Beat ; Tsangaris, Manos ; Appelt, Siegrun ; Belsole, Franco ; Bier, Rolf ; Blum, Agnes ; Breitenbach, Petra Von ; Burghart, Manuela ; Dallinga, Joke ; Eckermann, Silvia ; Eisler, Walter ; Eleveld, Fennanda ; Endlicher, Ursula ; Fuchs, Matthias ; Griebl, Stefan ; Heindl, Ursula ; Huber, Felix ; Van Huizen, Dineke P. ; Janecek, David ; Jena, Helga Von ; Jena, Achim Von ; Kaay, Gerard ; Karagandzic, Vesna ; Künzel, Monika ; Leitner, Reinhold ; Litschauer, Marie Therese ; Mosel, Kirsten ; Mugnaioli, Daniela ; Noack, Sigrid ; Nuti, Franco ; Onna, Tina ; Ostermeyer, Andrea ; Petkova, Vania ; Pisarik, Petr ; Rauch, Iwona ; Radulovic, Veronika ; Rähmi, Katharina ; Schenk, Michale ; Schleitzer, Angela ; Schneider, Martin ; Scholz, Francis ; Schumann, Regine ; Schröder, Johannes Lothar ; Smeets, Isabelle ; Van Soest, Trudy ; Steiger, Silvia ; Suk, Violet ; Tagwerker, Gerold ; Wende, Ovis ; Wojcik, Maria ; Böckler, Ursula ; Kleinefenn, Florian
Speciale kast : computerdiskette + CD
Duits
Engels
Italiaans
Nederlands
boek